Sound Absorption Behavior of Polyurethane Foam Composites with Different Ethylene Propylene Diene Monomer Particles - ZHU, Wenbo; CHEN, Shuming; WANG, Yebin; ZHU, Tongtong; JIANG, Yang (Archives of Acoustics, 2018)
Considering the environmental pollution caused by waste rubber, some measures should be taken to improve the utilization rate of waste rubber. In this study, the effect of Ethylene Propylene Diene Monomer (EPDM) particles in the polyurethane (PU) foams on sound absorption behavior is investigated for improving sound environment within vehicles and reducing the environment pollution. EPDM of different contents and hardness are used as fillers for producing foams with different pore morphologies and sound absorption properties. The results show adds EPDM to foam would produce smaller pores, higher density and bigger air-flow resistivity. Simultaneously, there are better sound absorption properties of the PU foam composites in the medium frequency region and the better value can be obtained at the lower frequency with the content of EPDM increasing. The hardness of EPDM also shows better influence on sound absorption properties, especially in the medium frequency region. It means the foam pore morphologies have influence on sound absorption properties.